2017
DOI: 10.1038/ncomms15124
|View full text |Cite
|
Sign up to set email alerts
|

ISCA1 is essential for mitochondrial Fe4S4 biogenesis in vivo

Abstract: Mammalian A-type proteins, ISCA1 and ISCA2, are evolutionarily conserved proteins involved in iron–sulfur cluster (Fe–S) biogenesis. Recently, it was shown that ISCA1 and ISCA2 form a heterocomplex that is implicated in the maturation of mitochondrial Fe4S4 proteins. Here we report that mouse ISCA1 and ISCA2 are Fe2S2-containing proteins that combine all features of Fe–S carrier proteins. We use biochemical, spectroscopic and in vivo approaches to demonstrate that despite forming a complex, ISCA1 and ISCA2 est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
119
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(127 citation statements)
references
References 59 publications
(84 reference statements)
8
119
0
Order By: Relevance
“…The first studies on the mitochondrial [4Fe‐4S] cluster assembly step showed that three human proteins ISCA1, ISCA2, and IBA57 are required for this process . This functional association has been revisited in a recent work , which showed that ISCA2 and IBA57 are not required under standard physiological conditions for the maturation of mitochondrial [4Fe‐4S] proteins. Therefore, the so far available in vivo data do not provide a clear picture on how the three proteins operate in the cell for assembling a [4Fe‐4S] cluster.…”
Section: Discussionmentioning
confidence: 99%
“…The first studies on the mitochondrial [4Fe‐4S] cluster assembly step showed that three human proteins ISCA1, ISCA2, and IBA57 are required for this process . This functional association has been revisited in a recent work , which showed that ISCA2 and IBA57 are not required under standard physiological conditions for the maturation of mitochondrial [4Fe‐4S] proteins. Therefore, the so far available in vivo data do not provide a clear picture on how the three proteins operate in the cell for assembling a [4Fe‐4S] cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, overexpression of ISC2 in an ISCU1 knock-down background in mouse cells showed that ISCA1, but not ISCA2, was essential for the [4Fe–4S] cluster assembly, since ISCU2 could not rescue the [4Fe–4S] defect caused by silencing of ISCU1 [89]. Regardless, the two scaffold proteins in mouse and human interact with each other in vitro [89, 109], although only ISCU2 was able to bind IBA57 [89]. …”
Section: Fe–s Cluster Machineries: a Brief Overviewmentioning
confidence: 99%
“…ISCA1 knockout resulted in developmental block in embryos at 8.5 days and caused embryonic lethality (Figure ). The ISCA1 protein accepts Fe/S from a scaffold protein and transfers it to the respiratory complex . The Fe/S is necessary for the stability of the mitochondrial Fe/S containing proteins of the respiratory complex in eukaryotic cells .…”
Section: Discussionmentioning
confidence: 99%
“…The Fe/S is necessary for the stability of the mitochondrial Fe/S containing proteins of the respiratory complex in eukaryotic cells . ISCA1 knockdown by rAAV‐mediated shRNA resulted in a substantial decrease in Succinate Dehydrogenase Complex Iron Sulfur Subunit B (SDHB), NADH Dehydrogenase Fe‐S Protein 3 (NDUFS3) and NADH Dehydrogenase (Ubiquinone) Fe‐S Protein 5 (NDUFS5) in skeletal muscle . NDUFA9 is a Fe/S‐containing protein of the mitochondrial respiratory chain complex I and is essential for assembling and stabilizing complex I .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation